Incomplete phase metasurface for wavefront reconstruction - Liu, Qiyao (2024)
Metasurfaces consisting of subwavelength elements exhibit unparalleled flexibility in light manipulation in terms of phase, amplitude, and/or polarization at ultrathin dimensions. Typically, a continuous and complete phase distribution covering a full 2π range is required in metasurface design to produce the performance of conventional optical components, such as gratings, lenses, and beam splitters. However, an incomplete phase, i.e., with phase change less or larger than 2π, can provide additional degrees of freedom for optical wavefront reconstruction. This article shows that designed metagratings, which unlocked the 2π phase constraint in supercell designs, achieved arbitrary control of the intensity ratio between any adjacent diffraction orders, while keeping the diffraction directions consistent with those of conventional gratings. Four metagratings, as representatives, with different phase ranges in the supercell, i.e., π, 2π, 3π, and 4π, have been designed and fabricated to demonstrate the diffraction intensity redistribution capability of metagratings. The 0th- and the 1st-order splitting ratios measured in experiments can reach 0.07 to 24.8, which is a hard task for traditional grating devices. Using a simple design methodology, incomplete phase metasurfaces hold great promise for developing various functional ultrathin nanophotonic devices, such as controllable beam splitters, spectrometers, and multifoci metalens.